Restriction Factors: From Intrinsic Viral Restriction to Shaping Cellular Immunity Against HIV-1 - Colomer-Lluch, Marta; Ruiz, Alba; Moris, Arnaud; Prado, Julia G. (Frontiers in Immunology, 2018)
Antiviral restriction factors are host cellular proteins that constitute a first line of defense blocking viral replication and propagation. In addition to interfering at critical steps of the viral replication cycle, some restriction factors also act as innate sensors triggering innate responses against infections. Accumulating evidence suggests an additional role for restriction factors in promoting antiviral cellular immunity to combat viruses. Here, we review the recent progress in our understanding on how restriction factors, particularly APOBEC3G, SAMHD1, Tetherin, and TRIM5α have the cell-autonomous potential to induce cellular resistance against HIV-1 while promoting antiviral innate and adaptive immune responses. Also, we provide an overview of how these restriction factors may connect with protein degradation pathways to modulate anti-HIV-1 cellular immune responses, and we summarize the potential of restriction factors-based therapeutics. This review brings a global perspective on the influence of restrictions factors in intrinsic, innate, and also adaptive antiviral immunity opening up novel research avenues for therapeutic strategies in the fields of drug discovery, gene therapy, and vaccines to control viral infections.